2014
DOI: 10.1515/jag-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Geo-Monitoring Using Image Assisted Total Stations

Abstract: Image Assisted Total Stations (IATS) unify geodetic precision of total stations with areal coverage of images. The concept of using two IATS devices for high-resolution, long-range stereo survey of georisk areas has been investigated in the EU-FP7 project DE-MONTES (www.de-montes.eu). The paper presents the used methodology and compares the main features with other terrestrial geodetic geo-monitoring methods. The theoretically achievable accuracy of the measurement system is derived and veri ed by ground truth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 8 publications
0
32
0
3
Order By: Relevance
“…Next, the vertical angular conversion factor of the telescope camera of the Leica MS50 was calibrated, which allows us to convert derived displacements from the pixel unit to the metric unit. In addition, the Fourier series (equation (15)) as a linear regression model and an AR process (equation (16)) as a coloured noise model were employed to estimate amplitudes and frequencies with high accuracy, assuming the white-noise components to follow a scaled t-distribution with an unknown scale factor and unknown degree of freedom. To estimate the model parameters by means of the GEM algorithm described in the preceding section, the number M of Fourier frequencies and the model order p of the AR process were specified beforehand.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, the vertical angular conversion factor of the telescope camera of the Leica MS50 was calibrated, which allows us to convert derived displacements from the pixel unit to the metric unit. In addition, the Fourier series (equation (15)) as a linear regression model and an AR process (equation (16)) as a coloured noise model were employed to estimate amplitudes and frequencies with high accuracy, assuming the white-noise components to follow a scaled t-distribution with an unknown scale factor and unknown degree of freedom. To estimate the model parameters by means of the GEM algorithm described in the preceding section, the number M of Fourier frequencies and the model order p of the AR process were specified beforehand.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…To compare the Leica MS50 and the LT, we can calculate the displacements for the Leica MS50 measurements based on equation 12and then input the displacements to equation (15) to calculate the amplitude (mm) and the frequency (Hz), respectively. Concerning the comparison of the Leica MS50 and the PSVC, we note that the output of the latter consists of acceleration measurements; we can calculate accelerations for the Leica MS50 measurements based on equation (13) and then use equation (15) to calculate the amplitude (m/s 2 ) and the frequency (Hz). However, it is also possible to calculate displacements from the acceleration measurements via double integration from equation (15).…”
Section: Displacement and Vibration Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, these are Global Navigation Satellite Systems (GNSS), Terrestrial Positioning Systems (TPS), Terrestrial Laser Scanners (TLS), (Stereo) Photogrammetry (SP) and Ground-Based Synthetic Aperture Radar (GB-SAR). As shown in [2], these methods generally differ from each other in cost, spatial and temporal resolution, range, dependence from weather or light conditions, energy and communication link requirement as well as in the necessity to access the possibly endangered surveillance area. However, this also implies that they can complement each other.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous examples have demonstrated that terrestrial, airborne, or satellite image based methods are suitable for producing displacement fields of landslides. These studies used subsequent images of two IATS devices in stereo configuration [2,4] or subsequent images of one camera and one ''static" digital surface model (DSM) -mostly derived from aerial laser scanning -to generate 3D information [5][6][7]. As a result, the most limiting factors of the final accuracy are small movements of the camera and the use of a mono-temporal DSM [6].…”
Section: Introductionmentioning
confidence: 99%